COMPARISON OF REAL COSTS OF MORTGAGE FINANCING: A COMPARATIVE STUDY OF FIXED MARGINS OF BANK SYARIAH INDONESIA (BSI) WITH FLOATING INTEREST RATES OF CONVENTIONAL BANKS - Taufikur Rohman; Muhammad Wildan Muttaqin (Nurul Jadid University, 2026)
The development of Islamic banking in Indonesia has accelerated following the merger of Bank Syariah Indonesia (BSI), but remains fraught with debate over the high financing margins compared to conventional bank interest rates. This study aims to analyze and compare the real costs of financing Home Ownership Loans (KPR) between BSI and conventional banks using the pure annuity method, assuming extreme margin levels and non-promotional interest rates for a 10-year term. The research approach used is an exploratory case study with qualitative methods, supported by secondary data from official banking reports and financing calculation simulations. The results show that conventional mortgages tend to result in lower total costs under stable interest rates, but this advantage is conditional due to the risk of floating interest rates. In contrast, Islamic financing at BSI offers installment certainty and protection from repricing risk through fixed margins. These findings confirm that differences in financing costs reflect differences in risk structures and pricing mechanisms, not simply the cost of financing products.